Insurance coverage change and survivorship care among young adult survivors of childhood cancer. (7th September 2021) - Mobley, Erin M.; Kim, Sue E.; Cousineau, Michael; Tsui, Jennifer; Miller, Kimberly A.; Tobin, Jessica; Freyer, David R.; Milam, Joel E.
Abstract: Objective: To (1) characterize change in type of insurance coverage among childhood cancer survivors from diagnosis to survivorship and (2) examine whether insurance change is associated with cancer‐related follow‐up care utilization. Data Sources: Participants in this study were derived from the Project Forward study, a population‐based, observational study of childhood cancer survivors in Los Angeles County that used California Cancer Registry data to identify participants. Study Design: Multivariable logistic regression models incorporating survey nonresponse weights estimated the change in the marginal predicted probabilities of insurance change and survivorship care, adjusting for demographic, socioeconomic, and clinical covariates and clustering by treating hospital. Data Collection/Extraction Methods: Study participants were diagnosed with cancer who were younger than age 20 years while living in Los Angeles County from 1996 to 2010 and were older than the age 18 years at the time of survey participation, from 2015 to 2017 ( N  = 1106). Principal Findings: Most participants were 18–26 years of age, male, diagnosed before 2004, Hispanic/Latino race/ethnicity, single, without children, highly educated, not employed full time, and lived with their parents at survey. Almost half ( N  = 529) of participants experienced insurance change from diagnosis to survivorship. Insurance change was associated with insurance coverage at diagnosis, as those who were uninsured were most likely to experience change and gain coverage during survivorship (by 51 percentage points [ppt], standard error [SE] of 0.05). Survivors who experienced any change had decreased probability of reporting a recent cancer‐related follow‐up care visit, a disparity that was magnified for those who lost insurance coverage (−5 ppt, SE 0.02 for those who gained coverage; −15 ppt, SE 0.04 for those who lost coverage). Conclusions: Insurance coverage change was associated with lower cancer‐related follow‐up care utilization. Indeed, survivors who experienced any insurance coverage change had decreased probability of having a cancer‐related follow‐up care visit, and this was magnified for those who lost their insurance coverage.